PERANCANGAN SISTEM INFORMASI EVALUASI PROSES PEMBELAJARAN BERBASIS WEB DI FAKULTAS TEKNOLOGI DAN KOMPUTER UNIVERSITAS WIDYA DHARMA KLATEN - Adri Brawijaya, David; Sulistyowati, Istri; Niken Retnowati, (Journal of Computer Science and Technology (JCS-TECH), 2024)
The development of information technology has brought significant changes in many fields, including education, including the learning process at the Faculty of Technology and Computers, especially Information Engineering at Widya Dharma University, Klaten. Evaluating the learning process is important to ensure the quality of education provided to students. However, the evaluation process carried out manually is often time-consuming and inefficient. Therefore, it is necessary to have an information system created specifically for learning evaluation. This research uses the Rapid Application Development (RAD) system development method and black box testing along with questionnaires as the testing system. This system was created using the PHP and Javascript programming languages, with the final result being a Learning Process Evaluation Information System which will have several features, including collecting and analyzing evaluation data, as well as reporting evaluation results. It is hoped that the results of this research can improve the quality of the learning process at the Faculty of Technology and Computers, especially in Informatics Engineering. With an efficient and integrated Learning Process Evaluation Information System, it is hoped that lecturers and academic staff can easily correct weaknesses in the learning process, as well as provide good feedback to students so that conditions that are conducive to learning can be created.